The Indian Mecistoscelini (Insecta, Heteroptera, Miridae, Mirinae): A preliminary review - Yeshwanth, H. M.; Chérot, F. (Zootaxa, 2019)
The tribe Mecistoscelini of the subfamily Mirinae (Insecta, Heteroptera: Miridae) from India is reviewed. Three genera and six species are cited from the country and are keyed, illustrated and diagnosed. Mystilus manipurensis n. sp. is described from Manipur. The following new synonymy is established: Mystilus antrami Distant, 1909 = Mystilus manni Distant, 1909. Mecistosceloides tonkinensis Carvalho, 1992 is reported for the first time from India.